2021
DOI: 10.1093/jrr/rrab013
|View full text |Cite
|
Sign up to set email alerts
|

Rectal dose-sparing effect with bioabsorbable spacer placement in carbon ion radiotherapy for sacral chordoma: dosimetric comparison of a simulation study

Abstract: It is difficult to treat patients with an inoperable sarcoma adjacent to the gastrointestinal (GI) tract using carbon ion radiotherapy (C-ion RT), owing to the possible development of serious GI toxicities. In such cases, spacer placement may be useful in physically separating the tumor and the GI tract. We aimed to evaluate the usefulness of spacer placement by conducting a simulation study of dosimetric comparison in a patient with sacral chordoma adjacent to the rectum treated with C-ion RT. The sacral chor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In these cases, a spacer that physically separates the tumor from the GI tract or other OARs may be useful (23,24). Using Gore-Tex sheets is one option in spacer placement but, recently, another option has emerged, use of a bioabsorbable polyglycolic acid (PGA) spacer which was developed in Japan (25,26). Using a Gore-Tex sheet as a spacer enables higher dose administration of C-ion RT for tumor control, even in cases of re-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, a spacer that physically separates the tumor from the GI tract or other OARs may be useful (23,24). Using Gore-Tex sheets is one option in spacer placement but, recently, another option has emerged, use of a bioabsorbable polyglycolic acid (PGA) spacer which was developed in Japan (25,26). Using a Gore-Tex sheet as a spacer enables higher dose administration of C-ion RT for tumor control, even in cases of re-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The safety of the PGA spacer has been reported [ 8 ], and another report of dosimetric comparison in a simulation study revealed that the PGA spacer improves dose distribution [ 10 ]. In this case, the tumor was close to the GI tract, and the PGA spacer was inserted, resulting in a reduced C-ion RT dose for the GI tract, and the treatment was safely performed.…”
Section: Discussionmentioning
confidence: 99%
“…However, C-ion RT cannot be performed for tumors close to or attached to the gastrointestinal (GI) tract due to the high risk of severe toxicity except with the surgical insertion of a spacer that physically separates the tumor from the GI tract. The spacer stops the C-ion beams at the distal end or reduces the radiation dose to the lateral penumbra by keeping a distance from the GI tract [ 8 , 9 , 10 , 11 ]. Previously, Gore-Tex sheets were used as spacers, and a favorable clinical result for C-ion RT patients was reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, patients with tumors infiltrating the rectum or tumors located with little-to-no space for inserting a spacer (eg, pelvic floor) were not suitable for insertion of a spacer that physically separates the tumor and the rectum to avoid severe rectal toxicities. 8 , 9 Therefore, to treat pelvic recurrences of rectal cancer without causing severe toxicities in cases where the tumor infiltrates or compresses the rectum, lowering the administration dose, rectal dose adjustment, and colostomy before C-ion RT might be necessary.…”
Section: Introductionmentioning
confidence: 99%